Lower Gastrointestinal Bleeding in Chronic Hemodialysis Patients - Fahad Saeed; Nikhil Agrawal; Eugene Greenberg; Jean L. Holley (International Journal of Nephrology)
Gastrointestinal (GI) bleeding is more common in patients with chronic kidney disease and is associated with higher mortality than in the general population. Blood losses in this patient population can be quite severe at times and it is important to differentiate anemia of chronic diseases from anemia due to GI bleeding. We review the literature on common causes of lower gastrointestinal bleeding (LGI) in chronic kidney disease (CKD) and end-stage renal disease (ESRD) patients. We suggest an approach to diagnosis and management of this problem.